Talent Management and its Effect on Employee Engagement: A Field Study on Islamic Banks Operating in the Capital Municipality of Sana'a - Yemen - Khosrof, Amaal Motaher Abdo (University of Science and Technology, Sana'a, 2024)
This study aimed to identify the impact of talent management (TM) (talent attraction, talent development and talent retention) on employee engagement (EE) (vigor, dedication and absorption) in islamic banks operating in the Capital Municipality of Sana’a, Yemen, consisting of five islamic banks, registered in the Yemeni banking activity based on the Yemeni Central Bank reports issued in 2015. The study adopted a descriptive analytical method and used a questionnaire as a data collection instrument. The study population consisted of 1024 workers in islamic banks in Sana'a. Based on Krejcie and Morgan's sample table, the sample size was 280 employees, selected by using non-proportional stratified random sampling method. Out of 280 distributed questionnaires, 278 were retrieved and 276 were valid for statistical analysis. The data were analyzed using SPSS (V. 25). The results revealed that TM is practiced at a high level in banks under study through all its dimensions (talent attraction, talent development and talent retention). EE is also practiced at a high level in the surveyed banks, with vigor and dedication being higher than absorption. Results also indicated that TM has a significant positive impact on EE in islamic banks under study, except for talent retention, which has no significant effect. Moreover, there were significant differences among the sample responses about EE practiced attributed to gender, but not to age or educational qualification variables. Based on these findings, it is recommended that islamic banks should maintain and enhance the high level of EE among their employees, focusing on the factors that foster EE. Furthermore, the aforementioned banks should pay more attention to TM practices and provide the necessary means to attract, develop, and retain talented employees.
Keywords: Talent Management; Employee Engagement; Islamic Banks; Sana'a